An Efficient Synthesis of Novel 4-Aryl-2-thioxo-3,4-dihydro-1H-pyrimido[1,2-a][1,3,5]triazin-6(2H)-ones and Their Antibacterial Activity - Do Van Quy; Nguyen Van Hung; Nadezhda Stolpovskaya; Aleksey Kruzhilin; Svetlana S. Olshannikova; Marina Holyavka; Vladimir Sulimov; Khidmet Shikhaliev (Molbank, 2022)
New substituted 4-aryl-8-methyl-2-thioxo-1,2,3,4-tetrahydro-6H-pyrimido[1,2-a][1,3,5]triazin-6-one 8a–b and ethyl 4-aryl-6-oxo-2-thioxo-1,3,4,6-tetrahydro-2H-pyrimido[1,2-a][1,3,5]triazine-7-carboxylate 8c–e were synthesized by the reaction of the corresponding 4-oxopyrimidin-2-ylthioureas with arylaldehydes. The formation of only one regioisomer was proven using complex spectral data and its structure was characterized. It was found that the interaction of 6-amino-4-phenyl-3,4-dihydro-1,3,5-triazine-2(1H)-thione with ethyl acetoacetate and diethyl ethoxymethylenemalonate leads to the formation of the same regioisomer. That is, changing the sequence of stages in this cascade process does not affect the structure of the final reaction product. All synthesized compounds exhibit antibacterial activity against E. coli and S. aureus cultures at a concentration (MIC) of 256 µg/mL.